Case report: Dezocine’s rapid and sustained antidepressant effects - Wang, Han; Lyu, Nan; Zhao, Qian (Frontiers in Pharmacology, 2024)
Anhedonia and motivational impairments are cardinal features of depression, against which conventional antidepressants demonstrate limited efficacy. Preclinical investigations and extant clinical trial data substantiate the promise of opioid receptor modulators in addressing anhedonia, depression, and anxiety. While synthetic opioid agents like dezocine are conventionally employed for analgesia, their distinctive pharmacological profile has engendered interest in their potential antidepressant properties and translational applications. Herein, we present a case in which persistent bupropion treatment was ineffective.However, the incidental administration of a single low-dose intravenous injection of dezocine resulted in a rapid and sustained amelioration of depressive symptoms, particularly anhedonia and motivational deficits.Our findings posit a potentially novel role for the "legacy drug" dezocine.